Adjustable foldable table / Muhammad Akmal Abu Bakar - Abu Bakar, Muhammad Akmal (2022)
The globe is today confronted with a number of serious difficulties as a result of population increase and resource constraint. Due to overcrowding in urban areas, people are forced to live in compact spaces such as flats or apartments. Overcrowding in living quarters can lead to economic and social concerns, and limited material options not only reduce quality of life. Foldable furniture has evolved as one of the solutions for space sustainability as a result of all of these difficult difficulties. Foldable furniture can assist save space for the user. In order to tackle this challenge, a design for an adjustable folding table has been constructed for this study. The respondent was given a set of the questionnaire to provide comments on the design. In order to tackle this challenge, a design for an adjustable folding table has been constructed for this study. The respondent was given a set of the questionnaire to provide comments based on the design provided. The study's findings reveal that respondents agree with the factors of material, design, marketing, and product satisfaction. This study's goal has been accomplished. Most respondents approved of the product design.